PROTOTYPE PERAHU PENGANGKUT SAMPAH BERBASIS ARDUINO - Zani, Wahyu tafta; Suharyanto, Cosmas (LPPM Universitas Putera Batam, 2022)
In human daily life ca not be separated from the use of technology, the development of this technology must be followed by human resources. The more people, the more the need for raw materials and the more waste. Indiscriminate disposal of garbage can pollute the air, soil and water, as a result the quality of water in rivers will decrease and can cause disease. what if the cleaning of garbage carried out by humans takes a lot of time and energy to clean up the garbage. The purpose of this research is to make a waste transporter with a remote control. The garbage boat is designed using Arduino Uno R3 which is controlled via a microcontroller. There is a servo motor that functions as the propulsion of the boat arm that serves to transport garbage into the boat, and there is a DC motor that moves the boat to turn right and left, and move forward. This prototype was made to make it easier for humans to transport garbage with microcontroller control and reduce the efficiency of the time needed and the dangers that exist in the river. The results obtained from this design are the boat can move freely on the surface of the water and the servo motor as the arm drive for transporting garbage.